Molecular Determination of Sex from Down and Feather in Wild and Reared Monomorphic and Dimorphic Birds at Juvenile Age - Antonio Ciro Guaricci; Mario Cinone; Salvatore Desantis; Giovanni Michele Lacalandra; Maria Albrizio (Animals)
The inability to distinguish males from females in young birds is a major obstacle for pair formation in reintroduction–restocking programs and commercial–amateur breeding. Several techniques are employed to address this problem, but not all of them are suitable for juvenile subjects. Among the various tests applied for sex determination, polymerase chain reaction (PCR) is one of the genetic tools that seems to be most effective (rapid, not invasive and cheaper). In this study, DNA was extracted from down and feathers to make the procedure less stressful for nestlings. The DNA was amplified by PCR, and the amplicon was subjected to the restriction endonucleases procedure when the gender was not clearly identified by PCR alone. One hundred and fifty-three avian species were sexed using this procedure, including 27 for the first time. In all the nestlings and juveniles tested, sex was correctly identified; in fact, all pairs that reached sexual maturity during this study gave offspring.